Rancang Bangun Sistem Pengukur Konduktivitas Larutan Elektrolit Menggunakan Mikrokontroler AT89C51 - Sumariyah, Sumariyah; Yulianto, Tony; Priyono, Jumadi (BERKALA FISIKA, 2006)
A system of electrolyte conductivity measurement has been designed and realized using microcontroller AT89C51. The system run at the frequency 2.5 Mhz. The adventage of the system is conductivity sensor placed outside the sample liquid. The input of system is NaCl concentration and the output is conductivity value.The hardware of this system is built by a conductivity sensor, oscillator XR-2206, a frequency synthesizer IC CMOS 4046, an operational amplifier LM358, an analog to digital converter ADC 0804, a liquid crystal display Seiko M1632, and a microcontroller AT89C51. To control this electrolyte liquid conductivity measurement was used macro assembler machine language.The results of the experiment show that the test of variable oscillator function has linear regression equation Y = 0.56 X + 1.96, amplification of LM358 amplifier test is 3.39 and has linear regression equation Y = 3.28 X + 0.05, ADC0804 conversion function has linear regression equation Y = 51.29 X + 9.97. The test of measurement system was sown that instrument able to measure NaCl conductivity from 0.2 M until 2.0 M with linear regression equation Y = 67,63x + 6,37.